2023
DOI: 10.1039/d2tb01774a
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of micropatterned curvature-dependent FA heterogeneity on cytoskeleton tension and nuclear DNA synthesis of malignant breast cancer cells

Abstract: Breast cancer is considered as a worldwide disease due to the high incidence and malignant metastasis. Although numerous techniques have been developed well to conduct breast cancer therapy, the influence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The expression of collagen, fibronectin and laminin demonstrates the formation of adhesion anchorage between cells and extracellular matrix (ECM) [145,146]. The transmembrane adhesion protein, integrin primarily binds collagen and fibronectin to produce adhesion sites for cell attachment, which is beneficial for migration, division and differentiation of stem cells in the process of tissue regeneration [147][148][149][150]. It can also connect a series of intracellular anchor Fig.…”
Section: Advanced Gene Nanocarriers/scaffolds For Gene Therapy In Tis...mentioning
confidence: 99%
“…The expression of collagen, fibronectin and laminin demonstrates the formation of adhesion anchorage between cells and extracellular matrix (ECM) [145,146]. The transmembrane adhesion protein, integrin primarily binds collagen and fibronectin to produce adhesion sites for cell attachment, which is beneficial for migration, division and differentiation of stem cells in the process of tissue regeneration [147][148][149][150]. It can also connect a series of intracellular anchor Fig.…”
Section: Advanced Gene Nanocarriers/scaffolds For Gene Therapy In Tis...mentioning
confidence: 99%
“…Although tremendous efforts have been concentrated on chiral origin, development, and functions in diseases, little attention has been paid to the influence of intracellular chirality on nuclear mechanotransduction and DNA synthesis. Cells will spread their anisotropic cytoskeleton structures and present diversified morphologies based on microenvironment-induced biased cell nanomechanics, such as differentiated component, polar topography and asymmetrical matrix mechanics. The application of microfabrication technology provides the real possibility for controlling stable polar cell morphology, including chirality. Recently, multiple studies have reported that intracellular chirality can regulate some of the cell behaviors, for example, dynamic cytoskeleton chirality, directional epithelial migration, and biased cell left–right asymmetry. Compared to the influence of intracellular polarity on the kinematic behavior of cells, the effects of intracellular chirality on nuclear mechanotransduction and DNA synthesis remain unclear. Therefore, it is urgently desired to reveal the mechanism of mechanotransduction in chiral cells.…”
Section: Introductionmentioning
confidence: 99%